"Water-in-deep eutectic solvent" electrolytes enable zinc metal anodes for rechargeable aqueous batteries. (March 2019) - Zhao, Jingwen; Zhang, Jian; Yang, Wuhai; Chen, Bingbing; Zhao, Zhiming; Qiu, Huayu; Dong, Shanmu; Zhou, Xinhong; Cui, Guanglei; Chen, Liquan
Abstract: Metallic zinc (Zn) is one of the most promising anodes for aqueous batteries, but so far its applicability for rechargeable systems remains elusive, mainly owing to the free water-induced parasitic reactions. Here, we report a new "water-in-deep eutectic solvent (water-in-DES)" electrolyte (~30 mol.% H2 O in a eutectic mixture of urea/LiTFSI/Zn(TFSI)2 ; TFSI, bis(trifluoromethanesulfonyl)imide), in which all water molecules participate in DES's internal interaction (H-bonding and coordinating) network, leading to a suppressed reactivity with Zn anode from both thermodynamic and electrochemical aspects. Inheriting characteristics from aqueous and DES media, this electrolyte enables stable and reversible Zn plating/stripping with over twentyfold enhancement in cycling life compared to routine aqueous electrolytes, even at low rates. With these merits, a desirable rechargeability (>90% capacity retention after 300 cycles at 0.1 C) is achieved for a 1.92 V (average dicharge voltage) Zn/LiMn2 O4 battery, together with a practical energy density of 52 Wh/kg (pouch cell, 2 Ah, ~9.8 × excess Zn on anode). Graphical abstract: fx1 Highlights: The incompatibility between routine aqueous electrolytes and Zn anode was revealed. A "water-in-DES" electrolyte with organized eutectic network was first proposed, which enables a reversible Zn chemistry. A nonsynchronous Nernst modulation realizes a ~0.11 V upward shift in the voltage of Zn batteries.